Disaster Preparedness Among Healthcare Workers: An Ecohumanist Approach to Education and Training - Alghamdi, Mohammed; Baharudin, Mohd Rafee Bin; Mahadi, Razif Bin; Saliluddin, Suhainizam Muhamad (Journal of Ecohumanism, 2024)
Background: Disaster preparedness is critical in ensuring that healthcare workers (HCWs) are adequately prepared to respond to emergencies. This study explores HCWs’ disaster preparedness knowledge, skills, and educational needs from an ecohumanist perspective. It emphasizes sustainability, interdisciplinary learning, and community-based responses. Objective: The study assesses the disaster preparedness levels of HCWs and identifies gaps in their education and training. Methods: A cross-sectional survey was conducted with 214 valid responses. A structured questionnaire assessed disaster preparedness knowledge, skills, and educational needs, analyzed using descriptive statistics and inferential methods. Results: The findings suggest moderate to high levels of preparedness among HCWs, with gaps in areas such as disaster research knowledge and specialized training. A high need for community resource awareness was identified. Conclusion: The study highlights the importance of improving HCWs’ disaster preparedness through ecohumanist-based training programs that focus on sustainability, collaboration, and community resilience.